9-6x=45x-4

Simple and best practice solution for 9-6x=45x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-6x=45x-4 equation:


Simplifying
9 + -6x = 45x + -4

Reorder the terms:
9 + -6x = -4 + 45x

Solving
9 + -6x = -4 + 45x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-45x' to each side of the equation.
9 + -6x + -45x = -4 + 45x + -45x

Combine like terms: -6x + -45x = -51x
9 + -51x = -4 + 45x + -45x

Combine like terms: 45x + -45x = 0
9 + -51x = -4 + 0
9 + -51x = -4

Add '-9' to each side of the equation.
9 + -9 + -51x = -4 + -9

Combine like terms: 9 + -9 = 0
0 + -51x = -4 + -9
-51x = -4 + -9

Combine like terms: -4 + -9 = -13
-51x = -13

Divide each side by '-51'.
x = 0.2549019608

Simplifying
x = 0.2549019608

See similar equations:

| x^2-x+16=0 | | -9x^2+4x+21=0 | | 13x^2-131x-250=0 | | (2+xi)(3-2i)=12+5i | | 2x^2+9x-216=0 | | -x^4+3x^2+x=256 | | -2x+5/2=17 | | x/2+5x/6+x/4=380 | | 0.05x+0.20*300=0.10(x+300) | | 0.05x+0.20*100=0.10(x+100) | | (3x+4)(6x-1)= | | 2w+1(w)-45=0 | | 0.05x+0.20*100mL=0.10(x+100mL) | | (6x+4)(3x-1)= | | 40.77=y/5+2.4y+y/10 | | 12x+15-36-8x=0 | | 2(x^2+7x-141)=0 | | 21-2w-4-w^2=0 | | 2x=4000 | | 26-x=3(x-2) | | 2x*3=12x*4 | | -5x-11=41 | | 9(5x-2)=21 | | 3x/2+4x=22 | | 21x=42x | | 6x^2+6x+48=0 | | w^2-4-2w^2-2w+21=0 | | (5+v)(5v+2)=0 | | 7+4(6-5x)=3-16x | | 6s-1.5s+2.25s=40.50 | | -10(x-1)=10-1x | | -7x+8y=15 |

Equations solver categories